Atomic data and opacity calculations in La v–x ions for the investigation of kilonova emission spectra. Issue 2 (27th April 2022) - Carvajal Gallego, H; Berengut, J C; Palmeri, P; Quinet, P
ABSTRACT: A new set of radiative parameters for spectral lines in La v –x ions is reported in this paper. These data were determined through the use of a multiplatform approach involving three independent theoretical methods, i.e. the relativistic Hartree–Fock method including core-polarization corrections (HFR + CPOL), the multiconfiguration Dirac–Hartree–Fock (MCDHF) method, and the particle-hole configuration-interaction (PH-CI) method implemented in the AMBiT program. Based on cross-comparisons between the results obtained with these three methods, and from comparisons with the few previously published experimental and theoretical data, the most complete and reliable set of wavelengths, transition probabilities, and oscillator strengths was then used to determine the necessary opacities for the analysis of the spectra emitted in the early phases of kilonovae following neutron star mergers, i.e. for typical conditions corresponding to temperatures $T \gt 20\, 000 $  K, a density ρ = 10 −10  g cm −3, and a time after the merger t  = 0.1 d.